New-onset type 1 diabetes mellitus with diabetic ketoacidosis in a 12- months old indian toddler - Kaur, Dr Harshindar; Dr Kulwinder Kaur; Dr Aanshul Rai Gupta; Dr Avneet kaur; Dr Harjot Kaur; Dr Amandeep kaur (GMC Patiala Journal of Research and Medical Education, 2023)
The presentation of type 1 diabetes mellitus is very rare in infants and the classical symptoms are not present at this age group, so they are usually treated as the case of infection and associated with risk of high mortality especially if complicated with diabetic ketoacidosis (DKA). Type 1 diabetes can appear at any age but it appears at two noticeable peaks 4-7years of age and second peak between 10-14 years. This is the case of a 12-months old infant with new-onset type 1 diabetes mellitus, complicated with DKA at diagnosis and is reported in view of its rarity and elevated mortality even when diagnosed. Intravenous insulin was given and then shifted to subcutaneous insulin after 48 hours of admission. Patient was discharged in stable condition & is on regular checkup.